Deeper look into feedback practice in an Indonesian context: exploration of factors in undergraduate clinical settings - Estivana Felaza; Ardi Findyartini; Rita Mustika; Jenny Bashiruddin; Lucia RM Royanto; Joedo Prihartono; Subha Ramani (Korean Journal of Medical Education, 2023)
Purpose The practice of feedback is influenced by the characteristics of students, teachers, and the clinical environment. Most studies on feedback have been conducted in Western settings with different sociocultural backgrounds to Indonesia. This study explores feedback in Indonesian clinical clerkship using a sociocultural lens and aims to provide an exemplar of adaptive practice relevant to non-Western settings. Methods This qualitative study was conducted using an interpretive phenomenology approach. Data were collected through focus groups with students and teachers and interviews with program coordinators. Data were transcribed verbatim and grouped according to data sources, coded, and analyzed thematically. Results Themes identified from the focus group discussions and interviews were categorized as student, teacher, and environmental factors. Student factors include dependence on feedback, tendencies to use a group approach, difficulties recognizing social rules, a perceived lack of resilience, and tendencies to doubt praise. Factors related to teachers include a high level of expertise, being extremely busy, having a strong commitment, and being unsure of students’ acceptance of feedback. Clinical environment factors influence interactions between teachers and learners and include high power distance and collectivistic values. A safe environment is needed to ensure effective feedback interactions. Conclusion High power distance, collectivism, and generational characteristics of students likely impact feedback practice in clinical settings. Designing a safe environment is essential for effective feedback practice.